Water Compatible Multicomponent Cascade Suzuki/Heck–Aldol, Suzuki–Aldol–Suzuki, and Aldol–Suzuki–Aldol Reactions: An Ecofriendly Paradigm for Multiple CarbonCarbon Bond Formation in One Pot. Issue 44 (2nd October 2013) - Kumar, Rajesh; Richa,; Andhare, Nitin H.; Shard, Amit; Sinha, Arun K.
<x xml:space="preserve">Abstract</x> Aryls in hot water: A versatile strategy has been devised for the synthesis of biologically active biaryl(hetero)chalcones from readily available precursors (see scheme). The method is step, pot, and carbon economic, ligand‐free, devoid of toxic reagents/solvents, and has a wide substrate scope.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>